2016
DOI: 10.5005/jp-journals-10005-1387
|View full text |Cite
|
Sign up to set email alerts
|

Age Assessment in Children: A Novel Cameriere\'s Stratagem

Abstract: AimAge is one of the essential factors in establishing the identity of a person, especially in children. Age estimation plays an important part in treatment planning, forensic dentistry, legal issues, and paleodemographic research. The present study was an attempt to estimate the chronological age in children of Davangere population by using Cameriere’s India specific formula.Materials and methodsThis was a retrospective observational study to estimate the chronological age in children of Davangere population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…When the accuracy of this method was tested for males and females, non-significant results were obtained with a p value of 0.1613 on the left side of the OPG and a p value of 0.4322 on the right side of the OPG respectively. Similar results were obtained by Bagh et al and Attiguppe et al (Bagh et al 2014;and Attiguppe et al 2016). Non-significant results prove that gender does not influence age estimation.…”
Section: Discussionsupporting
confidence: 87%
“…When the accuracy of this method was tested for males and females, non-significant results were obtained with a p value of 0.1613 on the left side of the OPG and a p value of 0.4322 on the right side of the OPG respectively. Similar results were obtained by Bagh et al and Attiguppe et al (Bagh et al 2014;and Attiguppe et al 2016). Non-significant results prove that gender does not influence age estimation.…”
Section: Discussionsupporting
confidence: 87%
“…In a study from North China [37], the canine, 1 st premolar, and 2 nd molar were significant predictors of age estimation. Also, in an Indian study conducted by Attiguppe et al [59], the 1 st premolar was included in the regression equation as a significant contributor. In the Serbian population [42], it was found that the canine and 2 nd molar were the most significant variables.…”
Section: Discussionmentioning
confidence: 99%
“…Al respecto, Attiguppe et al . 28 establecieron una fórmula específica para niños de la India (Davangere) de 6 a 15 años, en la cual las variables que se utilizaron fueron N0 y X4, y se encontró un R 2 ajustado del 73,5%, lo cual indica que se debe prestar atención a la posible diferencia entre los niños de diferentes orígenes étnicos. De la misma manera, Sharma et al .…”
Section: Discussionunclassified